Th-232 Radiological Aspects of Carbonate Niobium Mining Waste Use as Agricultural Amendment - Rafaella Menezes Ayllon; Marcos R. Furlan; Thammiris Mohamad El Hajj; Paulo Sergio Cardoso Silva (Brazilian Journal of Radiation Sciences)
The use of mining residues in agriculture may be possible, as long as there be previous studies in different areas, one of them being the analysis of the involved radionuclides behavior. This study determined the concentrations of 232Th activity in soil, soil treated with lime, soil with carbonate residue from niobium mining, soil with the mixture of lime and carbonate, in two moments. The transfer factor of 232Th from the soil to the plant was analyzed, in this case, lettuce (n=20), in the different types of treatment and in two moments. The addition of carbonate to the soils did not significantly alter the levels of radioactivity for 232Th radionuclide in lettuce. The effective dose resulting from the lettuce ingestion varied from 0.09 to 0.3 µSv y-1.